Two-phase Material Point Method applied to the study of cone penetration. (December 2016) - Ceccato, Francesca; Beuth, Lars; Vermeer, Pieter A.; Simonini, Paolo
Abstract: This paper presents numerical simulations of Cone Penetration Test (CPT) in water-saturated soft soils taking into account pore pressure dissipation during installation. Besides modelling interaction between soil skeleton and pore fluid, the problem involves large soil deformations in the vicinity of the penetrometer, soil–structure interaction, and complex non-linear response of soil. This makes such simulations challenging. Depending on the soil's permeability and compressibility, undrained, partially drained or drained conditions might occur. Partially drained conditions are commonly encountered in soils such as silts and sand–clay mixtures. However, this is often neglected in CPT interpretation, which may lead to inaccurate estimates of soil properties. This paper aims at improving the understanding of the penetration process in different drainage conditions through advanced numerical analyses. A two-phase Material Point Method is applied to simulate large soil deformations and generation and dissipation of excess pore pressures during penetration. The constitutive behaviour of soil is modelled with the Modified Cam Clay model. Numerical results are compared with experimental data showing good agreement.